PENGARUH PARTISIPASI ANGGOTA TERHADAP PERKEMBANGAN MODAL PADA KOPERASI BINTANG SEJAHTERA DI DESA PRAJEGAN KECAMATAN SUKOREJO KABUPATEN PONOROGO - Rizki Purpintari (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2016)
The purpose of this study are to determine member participation at Bintang Sejahtera cooperation, to know Growth of Capital at Bintang Sejahtera cooperation and to know different influences member participation for Growth of Capital. Sampling technique that  is  used  is  satified  sampling. The  samples  are  all  member  in  Bintang  Sejahtera cooperation that to number 56 member. Observation used to know of background Bintang Sejahtera cooperaation, Interview used to know of member participation, and documentation used to know of Growth of Capital. In analyzing data the researcher use the methods of statistical analysis t test ( t test ) to test the manual calculation. The results so that before to be member participation average cost is 1292.71, while after to be member participation average cost is 1905.96. For the t test values obtained that there are different influences on the member participation of Growth of Capital. This means that for analysis t test, there are value obtained thit  is -143,232 while ttab  is 1,673. This Ho  is rejected, meaning that there are different influences on the member participationn of Growth of Capital at the Bintang Sejahtera cooperation.